The Exhaustion Triangle: How Psychosocial Risks, Engagement, and Burnout Impact Workplace Well-Being - Raquel Lara-Moreno; Adelaida Irene Ogallar-Blanco; Nancy Guzmán-Raya; María Luisa Vázquez-Pérez (Behavioral Sciences)
Employee burnout levels have risen due to teleworking, increased job demands, and the lack of clear boundaries between personal and professional life. This study evaluated burnout levels, occupational health (through the presence or absence of psychosocial risk factors), engagement, and well-being/job satisfaction in a sample of employees aged over 18 from varying sociodemographic backgrounds. Additionally, we sought to explore the relationships among these variables and their influence on workplace well-being. The sample comprised 112 employees aged 18 to 65 (of both genders). The instruments used included the Burnout Syndrome Scale (Maslach Burnout Inventory—Student Survey -MBI-SS-), the DECORE multidimensional questionnaire, the Utrecht Work Engagement Scale (UWES), and the General Work Well-Being Questionnaire (qBLG). The results indicated that overall workplace well-being levels are high, while the presence of psychosocial risk factors and burnout levels are moderate to low. Most variables correlated with each other in the expected directions. Furthermore, job well-being was inversely predicted by cynicism and burnout and positively predicted by support, engagement, and control. This study highlights the importance of workplace well-being and occupational health. Our findings suggest the need for intervention programs that include strategies to motivate employees, improve the work environment, and enhance stress coping mechanisms, among other areas.